PENGGUNAAN WEBSITE CHATGPT SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB MANDIRI - Nurul Izzati; Maulidi Maulidi; Bunga Alif Fitria (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2025)
Over time, various advanced technologies continue to emerge worldwide. Existing technologies also keep enhancing human life, making it more practical and convenient. In the field of education, for instance, there are numerous technologies accessible to students to improve their understanding of the subjects being studied. However, most of these technologies remain underutilized by learners despite their great potential to assist them. One example is AI technology on the ChatGPT website, which can function as a self-learning platform for studying foreign languages, including Arabic. Based on this premise, this research aims to explore and identify the features of ChatGPT that can support independent Arabic language learning. This study employs a descriptive qualitative research method by collecting data directly from the ChatGPT website and then analyzing and describing the findings. The research findings reveal that the ChatGPT website can serve as a medium for independent Arabic language learning through various features, including planning the Arabic learning process, practicing writing skills, enriching vocabulary and expressions in Arabic, translating texts, correcting writing errors, creating Arabic language test simulations, explaining language rules, and serving as a platform for Arabic language games.